2000
DOI: 10.1182/blood.v96.3.864
|View full text |Cite
|
Sign up to set email alerts
|

Successful in vivo purging of CD34-containing peripheral blood harvests in mantle cell and indolent lymphoma: evidence for a role of both chemotherapy and rituximab infusion

Abstract: Elimination of tumor cells (“purging”) from hematopoietic stem cell products is a major goal of bone marrow–supported high-dose cancer chemotherapy. We developed an in vivo purging method capable of providing tumor-free stem cell products from most patients with mantle cell or follicular lymphoma and bone marrow involvement. In a prospective study, 15 patients with CD20+ mantle cell or follicular lymphoma, bone marrow involvement, and polymerase chain reaction (PCR)–detectable molecular rearrangement received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(44 citation statements)
references
References 27 publications
2
39
1
2
Order By: Relevance
“…The efficacy of CHOP plus rituximab in both low‐risk and high‐risk patients with aggressive lymphoma also has been reported in a recent multicenter Phase II study 43. The addition of rituximab also may improve ASCT programs by intensifying the in vivo purging effect before PBPC harvesting, as has been reported by our group and others 44–46. Our preliminary experience with rituximab‐supplemented C‐HDS has yielded promising results with respect to both salvage and first‐line treatment of aggressive lymphoma 47.…”
Section: Discussionsupporting
confidence: 61%
“…The efficacy of CHOP plus rituximab in both low‐risk and high‐risk patients with aggressive lymphoma also has been reported in a recent multicenter Phase II study 43. The addition of rituximab also may improve ASCT programs by intensifying the in vivo purging effect before PBPC harvesting, as has been reported by our group and others 44–46. Our preliminary experience with rituximab‐supplemented C‐HDS has yielded promising results with respect to both salvage and first‐line treatment of aggressive lymphoma 47.…”
Section: Discussionsupporting
confidence: 61%
“…Our findings strengthen the evidence supporting the inclusion of rituximab in treatment regimens for patients undergoing ASCT for relapsed DLBCL. The results of earlier studies suggest that the addition of rituximab to the stem‐cell mobilization process acted as an in vivo purge of contaminated bone marrow, and when given after transplantation, as a treatment for minimal residual disease (Magni et al , 2000; Galimberti et al , 2003; Shimoni et al , 2003; Belhadj et al , 2004; Brugger et al , 2004). In this study, the addition of rituximab to the transplant regimen was found to improve PFS, regardless of disease status, according to PET/G scans; however, patients with no evidence of disease on scans at the time of transplantation seemed to derive more benefit from the addition of rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Only those patients who achieved CR went on to the consolidation phase of the programme. In contrast, patients with a PR were rapidly shifted to an HDS programme with in vivo purging by rituximab to avoid the reinfusion of malignant cells (Magni et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Relapsed and responding patients achieving less than CR after completion of the initial induction phase were promptly shifted to an HD, stem cell-supported sequential chemotherapy programme including rituximab (R-HDS) (Magni et al, 2000) (Table IB).To avoid the reinfusion of malignant cells in these patients, autologous stem cell contamination by occult BL cells was studied using CDR3 analysis by polymerase chain reaction (PCR) (Deane & Norton, 1991).…”
Section: Salvage Treatmentmentioning
confidence: 99%